1996
DOI: 10.1016/0029-7844(95)00476-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic treatment of psychiatric disease in pregnancy and lactation: fetal and neonatal effects

Abstract: Psychoactive medications may be used during pregnancy. Because data on safety are largely retrospective, treatment decisions must be weighed carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…[37,72] Alternatively, in patients with a history of repeated psychotic epi-sodes, maintenance antipsychotics may be indicated to prevent further relapses. It is probably best to avoid antipsychotics during the first trimester if possible.…”
Section: Resultsmentioning
confidence: 99%
“…[37,72] Alternatively, in patients with a history of repeated psychotic epi-sodes, maintenance antipsychotics may be indicated to prevent further relapses. It is probably best to avoid antipsychotics during the first trimester if possible.…”
Section: Resultsmentioning
confidence: 99%
“…Psychoactive drugs, which often are given for long‐term intervention, are of particular concern, especially during pregnancy, acute illness, and when the patient is undergoing pharmacologic treatment for other medical problems. Awareness of these factors particularly is important during pregnancy as placental membranes do not protect the fetus from psychoactive drugs, and all psychotropic medications cross the placental barrier (50–57).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…A specific malformation pattern has been proposed (51, 52), ‘fetal valproate syndrome’, consisting of heart defects and withdrawal syndrome (irritability, jitteriness, hypotonia, and difficulty eating) (53). Vajda & Eadie and Morrow et al found that the rate of major malformations in fetuses exposed to valproate alone or in combination with other epileptic drugs ranges between 15.2% and 17.1%, and between 6.2% and 9.0%, respectively.…”
mentioning
confidence: 99%
“…Valproate safety in breastfeeding. VPA concentrations range from less than 1% to 10% in breast milk and infant serum, and from undetectable levels to 40% in maternal serum (33, 53). Thrombocytopenic purpura and anemia were attributed to valproate exposure through placenta and breast milk (55).…”
mentioning
confidence: 99%